Generic Medicine: Current Scenario in India - Komal Mandlik,; Dr.Charushila Bhangale, (Asian Journal of Pharmaceutical Research and Development, 2025)
India’s generic medicine industry plays a pivotal role in enhancing healthcare accessibility and affordability, both domestically and globally. This review explores the evolution, regulatory framework, government initiatives, market dynamics, and future prospects of generic medicines in India. The introduction highlights the significance of generics in reducing out-of- pocket healthcare expenses, especially in a country where a large portion of the population lacks comprehensive insurance coverage. The paper then examines the rapid growth of the generic pharmaceutical market, driven by robust manufacturing capabilities, supportive policies, and increasing global demand. Government programs such as the Pradhan Mantri Bhartiya Janaushadhi Pariyojana (PMBJP) have significantly expanded the reach of affordable medicines through Jan Aushadhi Kendras. Regulatory bodies like the Central Drugs Standard Control Organisation (CDSCO) and frameworks such as Good Manufacturing Practices (GMP) ensure quality assurance, although challenges persist in enforcement and public perception. The review also discusses pricing pressures, competition, and the need for consistent quality control across manufacturers. Opportunities lie in expanding exports, developing biosimilars, and leveraging digital technologies and artificial intelligence to streamline production and distribution. The paper concludes by emphasizing the importance of sustained policy support, public awareness, and innovation to strengthen India’s position as the “pharmacy of the world.” This comprehensive analysis provides insights into the challenges and opportunities facing India’s generic medicine sector and outlines strategic directions for future growth and global leadership.